Penerapan Pendekatan Deep Learning untuk Meningkatkan Keterlibatan Siswa dan Hasil Belajar Bahasa Indonesia Kelas VI - Roosyidah Haniifah; Akbar Al Masjid (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to improve student engagement and learning outcomes in Indonesian Language through the use of a deep learning approach in Grade VI at SD Negeri Blubuk. The problem addressed in this study is the low level of active student participation and learning outcomes that have not yet reached the Minimum Mastery Criteria (KKTP). The research method used is Classroom Action Research (CAR) with the Kemmis and McTaggart spiral model, which includes the stages of planning, action, observation, and reflection conducted in two cycles. Data were collected through observation, interviews, learning outcome tests, and student engagement questionnaires. The data were then analyzed descriptively and comparatively using percentages and averages. The results show an increase in the average learning outcome score from 63.2 in the pre-action stage to 83.5 in Cycle II, with 100% classical mastery. The average student engagement score also increased from the medium category to very high across all emotional, cognitive, and behavioral dimensions. These findings indicate that the use of a deep learning approach contributes to improving student engagement and learning outcomes in the context of Indonesian Language learning at the elementary school level.